The Identification, Assessment, and Treatment of Adults Who Abuse Animals The AniCare Approach - Shapiro, Kenneth; Henderson, Antonia J.Z (Springer International Publishing : Imprint: Springer, 2016)
This book provides step-by-step guidance on how to identify, assess and treat adults who have abused animals. The theoretical framework employed is broad, encompassing cognitive behavioral, psychodynamic, attachment, and trauma-based theories. Organized by stages of therapy, the text discusses how to frame the therapy, establish a working relationship, deal with resistance, establishing accountability, clarifying values related to animals, and teaching self-management skills such as empathy, attachment, accommodation, reciprocity and nurturance. Additional materials are included or referenced, including an appendix of cases that illustrate the variety of client presentations and electronic supplementary material demonstrates role-played interviews and a workshop presentation.